A Syntactical Analysis of Phrased Used in Song Lyric Typa Girl By Blackpink - Ghafera Kamelia Zahrotuhayaty (Universitas Mathla'ul Anwar Banten, 2024)
This research is analyzing syntactical of phrases used in song lyrics. In order to explain the theory and draw conclusions from a multitude of previous studies, the approach for this study was a review of the literature. Securing relevant information and avoiding duplication of research are two steps in the process of doing a literature review. Many commonalities were discovered during analysis, indicating that syntactical analysis was covered in all five of the pieces. The article's objectives are based on an earlier piece in which the author employed tree diagram theory to analyze music lyrics. Concurrently, the writer discovered many variations, Three papers employed songs as the subject of their investigations, but each writer used songs in a unique way. There are other factors that may be employed, such as using song as the object and analyzing phrase usage in songs using a tree diagram, based on five articles that were examined in relation to the writer's study for this article. The author discovered a gap in the literature by concentrating on the syntactical analysis of song lyrics in the phrases of Typa Girl by Blackpink